Recommendations for Orthotic & Prosthetic Clinics and Workshops in COVID-19 Pandemic - Yar, Usama Bin (Europasian Journal of Medical Sciences, 2020)
Orthotics and Prosthetics is an emerging field in medical area for several past years. Recently, COVID-19 is out-breaked as an epidemic and regarding that there is a need of protocols for Orthotic and Prosthetic workplaces to manage against the spread of this disease. Till now, COVID-19 pandemic has given boundless strain on health-care services providers and assistive technology practitioners, whose defamation is hard to recover. So, it is necessary to remain open to promote health coverage and support to amputees and disables. As only in America there were 1.9 million amputees since 2006 and till now they must have been increased ultimately. Large number of amputees has been increased since few years in recent report of WHO and World Bank. To cater such large number of population, recommendations are suggested which not only covers the introduction to novel coronavirus but also describes the entire frame-work for organizations to regulate themselves in this current epidemic situation. The recommendations accommodate somehow all administrative and management steps with correlation of clinical and non-clinical aspects. Moreover, it emphasizes on quality maintenance, assuring patient support and preventive initiatives regarding COVID-19 pandemic. It is requested to take help from this article and make your efforts to continue to assist people in need during this time.